Extensive cerebellar involvement and cognitive impairment in COVID-19-associated acute necrotizing encephalopathy. (February 2021) - Ciolac, Dumitru; Crivorucica, Igor; Zota, Eremei; Gorincioi, Nadejda; Efremova, Daniela; Manea, Diana; Crivorucica, Veaceslav; Ciocanu, Mihail; Groppa, Stanislav A.
Neurological complications of the newly appeared severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are increasingly recognized. Here, we report a case of a young male presenting with a clinical and neuroimaging scenario of an acute necrotizing encephalopathy related to the coronavirus disease 2019 (COVID-19). This case is notable by its distinct pattern of magnetic resonance imaging findings of an extensive involvement of the cerebellum, and emergence of cognitive and behavioral impairment.